ChemInform Abstract: Designing Polar and Magnetic Oxides: Zn2FeTaO6 — In Search of Multiferroics. Issue 40 (30th September 2014) - Li, Man‐Rong; Stephens, Peter W.; Retuerto, Maria; Sarkar, Tapati; Grams, Christoph P.; Hemberger, Joachim; Croft, Mark C.; Walker, David; Greenblatt, Martha
Abstract The new polar and magnetic LiNbO3‐type title compound is obtained from stoichiometric mixtures of ZnO, Fe2O3, and Ta2O5 under high pressure (multi‐anvil press, 9 GPa, 1623 K, 1 h).